GRAMSCI IN LACLAU AND MOUFFE’S POST-MARXISM - P. Russo, Fiorella (2021)
The crisis of Marxism favored the formulations of questions on how to think about Politics, the State, and History within Marxist theory, in view of the rising social movements towards the end of the 20th century. In their book Hegemony and Socialist Strategy: Towards a Radical Democratic Politics, Ernesto Laclau and Chantal Mouffe propose answers based on elements from Gramsci’s political theory. This article analyzes Laclau and Mouffe’s review of Gramsci’s political theory in their aforementioned book. Moreover, it also studies the theoretical consequences that the authors draw from their considerations regarding the creation of a theory which aims to surpass both Gramsci’s political theory and Marxism.